ANALYSIS OF THE STRATEGY OF THE HEAD OF MADRASAH TSANAWIYAH NURUL ISLAM ALAI IN IMPROVING THE QUALITY OF LEARNING - Mutiara Khoirunnisa; Putri, Icha Meiella Sarni; Syarifuddin (Guruku: Jurnal Pendidikan Profesi Guru, 2025)
This study aims to analyse the quality management strategies implemented by the Head of Madrasah Tsanawiyah Nurul Islam Alai to enhance learning effectiveness. The topic was chosen due to the critical role of leadership in improving educational quality, particularly in madrasahs that often face challenges such as low learning outcomes, limited use of innovative methods, and insufficient supervision. A descriptive qualitative method with a case study approach was employed. Data were collected through in-depth interviews with the madrasah head, direct observations, documentation studies, and secondary sources such as relevant journals and books. Data analysis involved source criticism, data organisation, and conclusion synthesis. The findings reveal that the madrasah head applied Total Quality Management (TQM) strategies, focusing on improving learning facilities, teacher training, and collaboration with parents. Active community participation through regular meetings and communal activities served as key supporting factors. However, challenges such as inadequate infrastructure and a shortage of teaching staff hindered programme optimisation. To address these issues, the madrasah head submitted proposals for government assistance and recruited teachers from nearby schools. Positive impacts of these strategies included increased student engagement, better material comprehension, and enhanced teaching quality. The study concludes that visionary leadership, stakeholder collaboration, and participatory approaches are pivotal to successful educational quality management. These findings provide practical insights for madrasahs in designing adaptive quality improvement strategies, though contextual considerations are necessary for broader generalisation.